The Role of Alcohol Consumption and Smoking Habits in Increasing the Diabetes Mellitus Risk in Adult Men and Women with Central Obesity in Indonesia - diyan yunanto setyaji; Hiasinta Anatasia Purnawijayanti (Journal of Global Nutrition, 2021)
Central obesity is more predictive of measuring the risk of type 2 diabetes compared to anthropometric indicators of general obesity. The results of previous studies are still inconsistent and the causal relationship that had not been well explained between the determinant factors and the increasing incidence of diabetes mellitus. This study aims to determine the relationship between alcohol consumption and smoking habits in increasing the risk of diabetes mellitus in adult males and females who are central obesity in Indonesia. The analysis presented in this study was based on the data from a population-based, cross-sectional, nationally representative survey (Indonesian Basic Health Research 2018/RISKESDAS 2018). In total, 12726 men and 18637 women aged 18–65 years were enrolled. A validated questionnaire, smoking card, and alcohol card were used for the assessments. There was a significant difference (p <0.000) in the proportion of diabetes mellitus incidence between men and women in both age groups who consumed less than 1 pack of cigarettes or more than 1 pack per day. The age difference for the sexes did not show a statistically significant association with alcohol consumption of either under 5 servings or above 5 servings per day for the incidence of diabetes mellitus. Women with central obesity had an adjusted prevalence ratio of 1.7 times higher for diabetes mellitus than men. There were negative multiplicative interactions between sexes and smoking status (interaction PR = 0.685; 95% CI = 0.52-0.88) and cigarette exposure (0.65; 0.52-0.80) in women. The effects of alcohol consumption and their interactions with sex did not have a significant relationship. There is an increased risk of diabetes mellitus especially in women with central obesity. Alcohol consumption by people with central obesity has an interaction with gender in an increased risk of diabetes mellitus which is higher in women than men.